Microbiome-directed food to promote sustained recovery in children with uncomplicated acute malnutrition: protocol for a randomized controlled trial in Burkina Faso - Hermann Biénou Lanou; Jérôme Winetourefa Somé; Marie Arsène Aristide Koumbem; Seni Kouanda (BMC Nutrition)
Abstract Background Acute malnutrition still affects millions of children under five years of age globally each year and contributes to approximately half of all annual childhood deaths. A considerable proportion of patients who recover from acute malnutrition experience poor health and nutrition and eventually relapse after they are discharged from community management of acute malnutrition programs. A microbiota-directed complementary food (MDCF) showed a superior effect compared to standard ready-to-use supplementary food (RUSF) in terms of ponderal growth and potential benefit for bacterial taxa that were correlated with weight-for-height z-score (WHZ). This paper describes a protocol for the MDCF phase III trial on a larger African sample for promoting sustained recovery. Methods This study is an individually controlled open-label phase III trial to determine the efficacy of MDCF on programmatic and sustained recovery compared to standards RUTF and RUSF. Eligible MAM children will be randomly assigned to MDCF or RUSF and those with SAM to MDCF or RUTF. Supplementation and follow-up visits will be performed following national guidelines for acute malnutrition management. Primary outcomes are programmatic recovery at 12 weeks after enrollment and sustained recovery at 12 weeks after recovery. The secondary outcomes included the mean WHZ, weight-for-age z score, height-for-age z score change, average length of stay, nonresponse, failure and dropout. Discussion The present study is designed to investigate the efficacy of a microbiota-targeted food in treating acute uncomplicated malnutrition and preventing relapses. It will provide evidence as a phase III clinical trial. Trial registration Clinicaltrials.gov Protocol registration and results system (NCT05586139). Registered on 2022–10–14. https://register.clinicaltrials.gov/ .